Information Science and Applications (ICISA) 2016 [electronic resource] - Kim, Kuinam J.; Joukov, Nikolai; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book contains selected papers from the 7th International Conference on Information Science and Applications (ICISA 2016) and provides a snapshot of the latest issues encountered in technical convergence and convergences of security technology. It explores how information science is core to most current research, industrial and commercial activities and consists of contributions covering topics including Ubiquitous Computing, Networks and Information Systems, Multimedia and Visualization, Middleware and Operating Systems, Security and Privacy, Data Mining and Artificial Intelligence, Software Engineering, and Web Technology. The contributions describe the most recent developments in information technology and ideas, applications and problems related to technology convergence, illustrated through case studies, and reviews converging existing security techniques. Through this volume, readers will gain an understanding of the current state-of-the-art information strategies and technologies of convergence security. The intended readers are researchers in academia, industry and other research institutes focusing on information science and technology.
PART 1 Ubiquitous Computing -- PART 2 Networks and Information Systems -- PART 3 Multimedia and Visualization -- PART 4 Middleware and Operating Systems -- PART 5 Security and Privacy -- PART 6 Data Mining and Artificial Intelligence -- PART 7 Software Engineering -- PART 8 Web Technology -- PART 9 Internet of Things -- PART 10 ICT Convergence -- PART 11 Convergence of Healthcare and Information Technology.
Keywords: Engineering; Computer security; Data structures (Computer science).